2020
DOI: 10.18311/jbc/2020/26131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Beauveria bassiana and Metarhizium anisopliae isolates against Plutella xylostella (L.) under laboratory conditions

Abstract: Twenty isolates each of Beauveria bassiana and Metarhizium anisopliae were tested against the second instar larvae of Plutella xylostella through laboratory bioassay using larval dip method at the concentration of 1×10 7 conidia/ml. Higher larval mortality of 88.85% and 81.44%, were observed with NBAIR Ma-4 and NBAIR Ma-35 isolates of M. anisopliae and 77.36% with NBAIR-Bb-5a isolate of B. bassiana. Further studies on dose and time mortality with four isolates indicated lowest LC 50 value of 2.6×10 4 conidia/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Among bio insecticides, Halt was superior to Biolep and neem-based formulations. Nahar et al (2004) revealed that M. anisopliae isolate M34412 conidia in an oil formulation of diesel and sunflower oil at 7:3 ratio was the most effective in controlling H. armigera.…”
Section: Effect Of Bio-rational Insecticides and Bio-pesticides On Se...mentioning
confidence: 99%
“…Among bio insecticides, Halt was superior to Biolep and neem-based formulations. Nahar et al (2004) revealed that M. anisopliae isolate M34412 conidia in an oil formulation of diesel and sunflower oil at 7:3 ratio was the most effective in controlling H. armigera.…”
Section: Effect Of Bio-rational Insecticides and Bio-pesticides On Se...mentioning
confidence: 99%